The role of 18F-FDG PET/CT in management of paraneoplastic limbic encephalitis combined with small cell lung cancer: A case report. Issue 35 (August 2019) - Castagnoli, Helga; Manni, Carlo; Marchesani, Francesca; Rossi, Gloria; Fattori, Sara; Capoccetti, Francesca
Abstract: Rationale: Limbic encephalitis is one of the most common paraneoplastic neurological disorders (PND). The role of brain Fluorine-18-fluorodeoxyglucose position emission tomography/computed tomography (CT) in paraneoplastic limbic encephalitis (PLE) and of the whole body 18F-FDG PET/CT in this setting, remains still not well defined. Patient concerns: We report a case of a patient with chronic inflammatory rheumatism, psoriasis and Hashimoto thyroiditis and subsequent appearance of static and dynamic ataxia and episodic memory deficit who was diagnosed as PLE combined with small cell lung cancer (SCLC). Diagnoses: The diagnosis of SCLC was made with EBUS-TBNA of a mediastinal lymph node. Interventions: Whole-body 18F-FDG PET/CT was performed for the initial staging of SCLC, in the planning of radiotherapy treatment, to evaluate therapeutic response and in the follow-up. A dedicated brain scan was included to the same PET session. Whole-body contrast enhanced computed tomography (CT) and contrast enhanced whole-brain MRI were also performed. Outcomes: She was administered neoadjuvant chemioterapy with Cisplatin and Etoposide with concomitant radiotherapy treatment. Whole body 18F-FDG PET/CT showed a complete metabolic response already after 3 cycles of chemioterapy. Brain functional study showed a metabolic pattern characterized by the migration of hypermetabolism in the bilateral hippocampal areas during the therapeutic treatment, which correlated with the persistence of clinical symptoms. Lessons: In the era of personalized medicine and targeted therapy, this case highlights the importance of the 18F-FDG PET/CT study as an accurate tool to identify PLE and to guide the diagnostic work-up of the underlying tumor. Considering that most of these are 18F-FDG avid tumors and that the 18F-FDG PET/CT scan is often added to the diagnostic work-up when screening patients for malignancy, this functional imaging can play a decisive role.